OILINESS OF INDIVIDUAL HYDROCARBONS AND ITS INFLUENCE ON THE FORMATION OF SURFACE TRIBOFILMS UNDER FRICTION IN LOCALLY CONTACTING SURFACES - Melnyk, Volodymyr; Leusenko, Daria; Savchuk, Anatolii; Hryb, Dmytro; Kobzar, Nazarii (Problems of Friction and Wear, 2026)
The effect of bulk temperature of individual hydrocarbons (paraffinic, naphthenic, and aromatic) on the formation of self-generating organic films (SOP) was studied over the range from each fluid’s melting point to its boiling point. The results reveal a consistent pattern: for each hydrocarbon there exists a characteristic temperature, dependent on molecular weight and lying between its melting and boiling points, at which the intensity of SOP formation increases while the friction torque decreases. Tests with naphthenic hydrocarbons showed that, similar to paraffinic ones, they form SOP on the friction surfaces within a certain temperature interval. With increasing molecular weight, both the temperature of maximum SOP-formation intensity and the final film thickness increase. For aromatic hydrocarbons, the temperature dependence follows the same trend as for paraffinic and naphthenic hydrocarbons but with considerably lower formation intensity and smaller final thickness.